Persistence through Peril : Episodes of College Life and Academic Endurance in the Civil War South - Foster, Holly A.; Platt, R. Eric, 1981- (Book collections on Project MUSE., 2021)
"Contributions by Christian K. Anderson, Marcia Bennett, Lauren Yarnell Bradshaw, Holly A. Foster, Tiffany Greer, Don Holmes, Donavan L. Johnson, Lauren Lassabe, Sarah Mangrum, R. Eric Platt, Courtney L. Robinson, David E. Taylor, Zachary A. Turner, Michael M. Wallace, and Rhonda Kemp Webb. To date, most texts regarding higher education in the Civil War South focus on the widespread closure of academies. In contrast, Persistence through Peril: Episodes of College Life and Academic Endurance in the Civil War South brings to life several case histories of southern colleges and universities that persisted through the perilous war years. Contributors tell these stories via the lived experiences of students, community members, professors, and administrators as they strove to keep their institutions going. Despite the large-scale cessation of many southern academies due to student military enlistment, resource depletion, and campus destruction, some institutions remained open for the majority or entirety of the war. These institutions-"The Citadel" South Carolina Military Academy, Mercer University, Mississippi College, the University of North Carolina, Spring Hill College, Trinity College of Duke University, Tuskegee Female College, the University of Virginia, the Virginia Military Institute, Wesleyan Female College, and Wofford College-continued to operate despite low student numbers, encumbered resources, and faculty ranks stripped bare by conscription or voluntary enlistment. This volume considers academic and organizational perseverance via chapter "episodes" that highlight the daily operations, struggles, and successes of select southern institutions. Through detailed archival research, the essays illustrate how some southern colleges and universities endured the deadliest internal conflict in US history"--